2003
DOI: 10.1037/0022-006x.71.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child interaction therapy: A comparison of standard and abbreviated treatments for oppositional defiant preschoolers.

Abstract: Families of 54 behaviorally disturbed preschool-aged children (3 to 5 years) were randomly assigned to 1 of 3 treatment conditions: standard parent-child interaction therapy (PCIT; STD); modified PCIT that used didactic videotapes, telephone consultations, and face-to-face sessions to abbreviate treatment; and a no-treatment waitlist control group (WL). Twenty-one nondisturbed preschoolers were recruited as a social validation comparison condition. Posttreatment assessment indicated significant differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
173
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(188 citation statements)
references
References 51 publications
8
173
2
5
Order By: Relevance
“…Clinical experiments express that interaction therapy is concomitant with a significant improvement of children's destructive behaviors and parents' anxiety and leads to an increase in parents' confidence in their children's control of extreme behaviors (Abrahamse et al, 2012;Hood & Eyberg, 2003;Nixon, Sweeney, Erickson, & Touyz, 2003;Nixon, Sweeney, Erickson, & Touyz, 2004;Schuhmann, Foote, Eyberg, Boggs, & Algina, 1998). In two studies (Choate, Pincus, Eyberg, & Barlow, 2005), PCIT has been successfully used in decreasing separate anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experiments express that interaction therapy is concomitant with a significant improvement of children's destructive behaviors and parents' anxiety and leads to an increase in parents' confidence in their children's control of extreme behaviors (Abrahamse et al, 2012;Hood & Eyberg, 2003;Nixon, Sweeney, Erickson, & Touyz, 2003;Nixon, Sweeney, Erickson, & Touyz, 2004;Schuhmann, Foote, Eyberg, Boggs, & Algina, 1998). In two studies (Choate, Pincus, Eyberg, & Barlow, 2005), PCIT has been successfully used in decreasing separate anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Parenting practices influence a child's development, environment, and well being; which can lead to lifelong effects on the child (Landry, Smith & Swank, 2003). Providing parenting knowledge to ID/SA mothers will improve the maternal-child dyad (Kumpfer & Alvarado, 2003;Nixon, Sweeney, Erickson & Touyz, 2003). Parental involvement in the children's education is important in helping promote positive attitudes and behaviors.…”
Section: Residential Rehabilitation Programsmentioning
confidence: 99%
“…ParentChild Interaction Therapy uses in-vivo coaching within sessions to reinforce caregivers' use of skills, which also has been shown to be an important component of effective parent training programs (Kaminski, Valle, Filene, & Boyle, 2008). On average, intervention duration for standard PCIT is 12 weeks (Nixon & Sweeney, 2003).…”
Section: Family-focused Interventions For Young Children With Tbimentioning
confidence: 99%
“…As such, recent literature has begun to examine the use of a more intensive format of PCIT, which incorporates the core components in a time-limited manner. Overall, studies have found comparable effects between abbreviated PCIT (i.e., five face-to-face sessions alternated with five 30-min consultations) and standard PCIT (Nixon & Sweeney, 2003) at a 6-month follow-up, as well as equivalent or better outcomes when utilizing timelimited PCIT with families at risk or with a history of maltreatment (Thomas & ZimmerGembeck, 2012). Further, Graziano and colleagues (2014) provided evidence for the use of a brief and intensive version of PCIT (ten 90-minute sessions every weekday across 2 weeks) and suggested future research should examine whether intensive interventions can be effective for high-risk families (e.g., low SES and minority group status), who often have more barriers typically resulting in dropout (Graziano et al, 2014;Lavigne et al, 2010).…”
Section: Consistent With Recommendations To Examine Established Intermentioning
confidence: 99%